Pengaruh Lingkungan Kerja Non Fisik Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Yayasan Populi Center Jakarta Selatan - Aji Jujun Julkipli; Andri Priadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study is to determine the effect of non-physical work environment and work motivation, both partially and simultaneously, on employee performance at the Work Unit of the Populi Center Foundation, South Jakarta. This study used a quantitative method with a population of 60 employees and employed a total sampling technique, meaning that the entire population was used as the sample. The results show that the t-test value for the non-physical work environment variable is positive, with t count > t table (3.328 > 2.002). This finding is supported by a significance value of 0.000 < 0.05. Therefore, Ho is rejected and H1 is accepted, indicating that there is a significant effect of the non-physical work environment on employee performance. Furthermore, the t-test value for the work motivation variable is positive, with t count > t table (2.933 > 2.002), and a significance value of 0.000 < 0.05. Thus, Ho is rejected and H1 is accepted, meaning that work motivation has a significant effect on employee performance. Based on the ANOVA test, the calculated F value (F count) is 91.416, while the F table value at α = 0.05 and n = 57 is 2.77. Since F count > F table (91.416 > 2.77) and the significance level is 0.000 < 0.05, it can be concluded that the non-physical work environment (X1) and work motivation (X2) together have a significant effect on employee performance (Y).